1992
DOI: 10.1016/0960-0760(92)90317-c
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of steroidogenic enzyme gene expression in Leydig cells

Abstract: In normal mouse Leydig cells, steady state levels of mRNA of CYP11A, 3β-hydroxysteroid dehydrogenase Δ⁵- >Δ⁴-isomerase (3βHSD), and CYP17 are differentially regulated. There is high basal expression of 3βHSD and CYP11A mRNA, while expression of CYP17 mRNA is absolutely dependent on cAMP stimulation. cAMP is required for maximal expression of all three enzymes. The expression of CYP11A in normal mouse Leydig cells is repressed by glucocorticoids. Glucocorticoids also repress both basal and cAMP-induced expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Many in vitro studies using several Leydig cell types have confirmed and extended the above results (reviewed in Payne et al 1992, Saez 1994, Payne & O'Shaughnessy 1996. The main conclusions from both in vivo and in vitro studies are the following.…”
Section: Endocrine Regulationmentioning
confidence: 65%
“…Many in vitro studies using several Leydig cell types have confirmed and extended the above results (reviewed in Payne et al 1992, Saez 1994, Payne & O'Shaughnessy 1996. The main conclusions from both in vivo and in vitro studies are the following.…”
Section: Endocrine Regulationmentioning
confidence: 65%
“…By checking the expression of four well-known steroidogenesis genes including Tspo [16], Hsd3b1 [17], Star [18], and Cyp11a1 [19], our data showed the possible involvement of post-PKA signaling in curcuminsuppressed steroidogenesis in Leydig cells. According to our data, the mRNA expression levels of Tspo and Hsd3b1 in MA-10 cells were not altered by both 8-brcAMP and curcumin ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro perfusion of the adult rat testis with testosterone or DHT leads to reduced de novo secretion of testosterone (Darney and Ewing, 1981). In this context, testosterone has been shown to act via the androgen receptor to repress the expression of both the C 17a -hydroxylase/C 17,20 -lyase gene and the 3β-hydroxysteroid dehydrogenase gene (Payne et al, 1992). In addition to this mechanism of product inhibition, it has been demonstrated recently that testosterone also inhibits its own biosynthesis via specific, competitive binding to C 17a -hydroxylase (Darney et al, 1995).…”
Section: A Endocrine Regulation Of Lc Functionmentioning
confidence: 99%